2022
DOI: 10.1155/2022/1087060
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges for Pastoral Beef Cattle Production in Ethiopia

Abstract: The beef cattle production sector plays a crucial role in the livelihoods of pastoral farmers in Ethiopia, and it is the main source of beef animals for domestic and foreign markets. As compared to other African countries, Ethiopia has a huge beef cattle population (65.35 million heads). However, the quality and quantity of beef, as well as per capita meat consumption of Ethiopians, are very low (8.4 kg/individual/year). In this sense, the goal of this review was to provide and synthesize the most validated sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…16,17 Bovine trypanosomosis is highly abundant and widespread throughout Ethiopia's most agricultural and fertile areas, particularly in the lowlands and major river basins of the Abay, Omo, Akabo, Didessa, Ghibe, and Baro. 18,19 The disease has been documented in several locations of the country, with prevalence rates ranging from 1.38% to 17.15% whereas only a few published studies have been found in Afar and Tigray. 20 Currently, 5 Glossina species, namely Glossina pallidipes, Glossina morsitans submorsitans, Glossina fuscipes, Glossina tachinoides, and Glossina longipennis, infest around 220 000 km 2 of the country's above-mentioned regions.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Bovine trypanosomosis is highly abundant and widespread throughout Ethiopia's most agricultural and fertile areas, particularly in the lowlands and major river basins of the Abay, Omo, Akabo, Didessa, Ghibe, and Baro. 18,19 The disease has been documented in several locations of the country, with prevalence rates ranging from 1.38% to 17.15% whereas only a few published studies have been found in Afar and Tigray. 20 Currently, 5 Glossina species, namely Glossina pallidipes, Glossina morsitans submorsitans, Glossina fuscipes, Glossina tachinoides, and Glossina longipennis, infest around 220 000 km 2 of the country's above-mentioned regions.…”
Section: Introductionmentioning
confidence: 99%
“…Small proportion of liveweight losses during draft service may be the result of the shorter period of the draft service and availability of improved feed resources. According to some other researchers [58,60], HCF systems are characterized as traditional market-oriented production systems.…”
Section: Quality Of Beef Produced From Oxen Reared In the Hararghe Ca...mentioning
confidence: 99%
“…B. Abebe et al (2022) note the significance of cattle breeding in Ethiopia as the main source of meat-producing animals for internal and external markets. Compared to other African countries, Ethiopia has a massive number of cattle (about 65 million heads), but the quality and quantity of beef consumed per capita is rather low (8.4 kg per year).…”
Section: Introductionmentioning
confidence: 99%